The upper extremity of the professional tennis player: muscle volumes, fiber-type distribution and muscle strength - Sanchis-Moysi, J.; Idoate, F.; Olmedillas, H.; Guadalupe-Grau, A.; Alayon, S.; Carreras, A.; Dorado, C.; Calbet, J. A. L. (Scandinavian Journal of Medicine & Science in Sports, 2010)
The effects of professional tennis participation on dominant and non-dominant upper extremity muscle volumes, and on fiber types of triceps brachii (lateral head) and vastus lateralis muscles were assessed in 15 professional tennis players. Magnetic resonance imaging (MRI, n=8) examination and dual-energy x-ray absorptiometry (DXA, n=7) were used to assess muscle volumes and lean body mass. Muscle fiber-type distribution assessed by biopsy sampling was similar in both triceps brachii (2/3 were type 2 and 1/3 type 1 fibers). The VL was composed of 1/3 of type 2 and 2/3 of type 1 fibers. The dominant had 12-15% higher lean mass (DXA/MRI) than the non-dominant (P<0.05). Type 1, 2a and 2x muscle fibers of the dominant were hypertrophied compared with the non-dominant by 20%, 22% and 34% (all P<0.01), respectively. The deltoid, triceps brachii, arm flexors and forearm superficial flexor muscles of the dominant were hypertrophied (MRI) compared with the non-dominant by 11-15%. These muscles represented a similar fraction of the whole muscle volume in both upper extremities. Dominant muscle volume was correlated with 1RM on the one-arm cable triceps pushdown exercise (r=0.84, P<0.05). Peak power during vertical jump correlated with VL muscle fibers's cross-sectional area (r=0.82-0.95, P<0.05).